Corrosion-resistant rebar and its production method
By designing corrosion-resistant reinforcement bars with specific elemental compositions and a controlled production process, the challenges of high production costs and difficulty associated with adding alloy elements like Cr, Ni, and Mo are addressed, resulting in bars with enhanced corrosion resistance and mechanical properties at a lower cost.
Patent Information
- Application Number
- JP2024557885
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-03-16
- Filing Date
- 2023-07-27
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2043-07-27
AI Technical Summary
The high cost and difficulty in production of corrosion-resistant reinforcement bars due to the need for adding alloy elements like Cr, Ni, and Mo to improve corrosion resistance.
Development of corrosion-resistant reinforcement bars with a composition of C: 0.03-0.15%, Si: 0.8-2.0%, Mn: 0.8-2.0%, Cu: 0.10-0.50%, P: 0.08-0.2%, S: 0.005-0.01%, and the remainder being Fe and inevitable impurities, without the addition of Cr, Ni, or Mo, achieved through a comprehensive design of alloy elements and a controlled production process.
The solution provides corrosion-resistant reinforcement bars that combine excellent corrosion resistance and mechanical properties with reduced production costs, effectively extending the useful life of construction projects in chlorine salt erosion environments.
Smart Images

Figure 2025513751000001 
Figure 2025513751000002 
Figure 2025513751000003
Abstract
Description
[Technical field]
[0001] The present application is in the field of steel smelting technology, and more particularly, relates to corrosion resistant reinforcing bars and methods for producing same.
[0002] This application claims priority to a Chinese patent application bearing application number 202310252937.7 and entitled "Corrosion-resistant rebar and its production method" filed with the China Patent Office on March 16, 2023, the entire contents of which are incorporated herein by reference. [Background technology]
[0003] The main cause of the insufficient durability of reinforced concrete structures is the corrosion of rebars. Conventional techniques improve the corrosion resistance of rebars by adding large amounts of alloying elements such as chromium, molybdenum, and nickel, but the high cost of the alloys and the difficulty of production make it difficult to popularize and apply on a large scale.
[0004] The Chinese patent document CN114790532A discloses an alloy corrosion-resistant rebar and a manufacturing method thereof. The alloy corrosion-resistant rebar contains, by weight, 0.05-0.25% C, 1.05-2% Si, 0.3-1.5% Mn, 0.5-2.5% Cr, 0.05-1% Ni, 0.001-0.005% O, 0.001-0.0035% S, 0.005-0.0035% Ti, and 0.005-0.0035% H. The alloy contains 0.1%, Al: 0.005-0.1%, V: 0.005-0.03%, Nb: 0.005-0.03%, and the remainder is Fe and unavoidable impurities, and the contents of Si and Mn satisfy 2≦Si / Mn≦5, the contents of Si and Cr satisfy 0.75≦Si / Cr≦1.5, and the contents of Ti and Al satisfy 0.02%≦Ti+Al≦0.2%. This corrosion-resistant rebar ensures good corrosion resistance without adding Mo elements by comprehensively designing elements such as Si, Ti, and Al, but it is necessary to add Cr and Ni elements, and the cost increases due to the high contents of Cr and Ni elements. Therefore, it is meaningful for this field to research and develop rebars that have good corrosion resistance without adding alloy elements such as Cr, Ni, and Mo. Summary of the Invention [Problem to be solved by the invention]
[0005] Therefore, the technical problem to be solved by this application is to provide a corrosion-resistant rebar and a method for producing the same in order to eliminate the deficiencies of the conventional technology that the production cost of rebars is high and production is difficult because of the need to add alloy elements such as Cr, Ni, and Mo to improve the corrosion resistance of rebars. [Means for solving the problem]
[0006] To this end, the present application provides the following technical solutions:
[0007] The present invention contains, by weight percent, C: 0.03-0.15%, Si: 0.8-2.0%, Mn: 0.8-2.0%, Cu: 0.10-0.50%, P: 0.08-0.2%, S: 0.005-0.01%, Nb≦0.1%, V≦0.2%, Ti≦0.1%, Al≦0.1%, and the remainder being Fe and unavoidable impurities, To provide a corrosion-resistant reinforcing bar having 0.6≦Si / Mn≦2.0 and 0.25%≦Cu+P+S≦0.62%.
[0008] The corrosion-resistant reinforcing bar is (1) The C content is 0.05 to 0.12%. (2) The Si content is 0.9 to 1.7%. (3) The Mn content is 0.9 to 1.8%. (4) The Cu content is 0.2 to 0.3%. (5) The P content is 0.11 to 0.18%. Satisfy at least one of the following:
[0009] The corrosion-resistant reinforcing bar is (1) The C content is 0.06 to 0.09%. (2) The Si content is 1.0 to 1.3%. (3) The Mn content is 1.0 to 1.5%. (4) The P content is 0.13 to 0.17%. Satisfy at least one of the following:
[0010] The present application provides a production process for said corrosion-resistant rebar, including the steps of smelting, refining, continuous casting, slab heating, and hot continuous rolling.
[0011] The continuous casting process includes: (1) Low-carbon steel mold powder with a carbon content of 0.15% or less is used, and the thickness of the mold powder layer is 8 to 10 mm; (2) The water flow rate of the crystallizer is 1950-2050 L / min. (3) The crystallizer has an electromagnetic stirring current of 330A-370A and a frequency of 3-5Hz, and the terminal has an electromagnetic stirring current of 380A-420A and a frequency of 10-12Hz; (4) The drawing speed is 2.5 to 3.5 m / min. Satisfy at least one of the following:
[0012] The smelting process includes: (1) The tapping temperature is 1600 to 1640°C. (2) The deoxidizing alloying of steel at tapping stage is carried out in the following order: silico-manganese, ferrosilicon and lime. The amount of the silicomanganese added is 10 to 30 kg / t, and the amount of the ferrosilicon added is 15 to 30 kg / t; (3) The bottom blowing pressure is 0.4-0.5MPa in the early stage and 0.3-0.4MPa in the later stage. Satisfy at least one of the following:
[0013] The early stage refers to the process from the start to the end of alloy addition. The later stage refers to the process from when the molten steel composition reaches the target composition to when smelting is completed.
[0014] In the slab heating step, the heating temperature is 1200 to 1250°C.
[0015] In the continuous hot rolling process, the temperature of the reinforcing bar transferred to the cooling bed is 850 to 900°C.
[0016] The refining step includes: (1) the smelting process includes the step of adding ferrophosphorus and copper; (2) The stirring time of the refining is 10 minutes or more. (3) The tapping temperature is 1580 to 1600°C. Satisfy at least one of the following:
[0017] The phosphorus content in the ferrophosphorus is 20 to 25 mass %, The amount of the ferrophosphorus added is 3 to 6 kg / t, The amount of copper added is 1.5 to 3.5 kg / t. Effect of the Invention
[0018] The technical solution of the present application has the following advantages:
[0019] 1. The corrosion-resistant rebar according to the present invention contains, by weight, C: 0.03-0.15%, Si: 0.8-2.0%, Mn: 0.8-2.0%, Cu: 0.10-0.50%, P: 0.08-0.2%, S: 0.005-0.01%, Nb≦0.1%, V≦0.2%, Ti≦0.1%, Al≦0.1%, and the remainder is Fe and unavoidable impurities, with 0.6≦Si / Mn≦2.0 and 0.25%≦Cu+P+S≦0.62%. In the present invention, alloy elements such as Si, Mn, Cu, P, and S are comprehensively designed, and the strengthening and corrosion-resistant effects of each element are comprehensively considered, thereby solving the problem of the deterioration of the corrosion resistance of steel due to the non-addition of Cr, Ni, and Mo, and reducing the production cost of the rebar. Each element acts in concert with a specific content to fully exert its corrosion resistance and strengthening effects, solving the problem of the prior art that corrosion resistance, mechanical properties and cost cannot be combined, and overcoming the technical prejudice that Cr, Ni or Mo must be added to improve corrosion resistance. In particular, the present application improves the chlorine salt corrosion resistance and strength-plasticity compatibility of steel materials through the synergistic combination of four elements, Si, Mn, Cu and S. The corrosion-resistant rebar according to the present application can combine corrosion resistance and low cost, overcoming the prior art problem of the difficulty in matching corrosion resistance properties and alloy cost, and greatly extending the service life of construction projects in chlorine salt corrosion environments.
[0020] C element plays a strengthening role, and if its content is too high, it is easy to form carbides, which reduces the corrosion resistance, plasticity, toughness and welding properties of the steel. Si element acts as a deoxidizer, which can greatly reduce the oxygen content in the steel and reduce the formation of oxide inclusions. High Si content is favorable to form silicate phase on the surface of the steel, preventing the penetration and accumulation of erosive media, and improving corrosion resistance properties. Si is also a strengthening element and a ferrite forming element, and its high content is favorable to adjust strength and plasticity, overcome the brittleness problem caused by too high Cu and P contents, and optimize mechanical properties. Too high Si content is unfavorable to welding. Mn can significantly improve the strength of steel through its solid solution strengthening action, and if its content is too high, the hardenability will be improved, and Mn and S are easy to form MnS inclusions, which will reduce the plasticity and corrosion resistance of steel. By controlling the Mn content and Cu element, Cu can consume S, inhibit the formation of MnS, prevent the occurrence of MnS corrosion behavior, and improve corrosion resistance. Cu is a corrosion-resistant element, and it concentrates in the rust layer to form S and CuS, improving corrosion resistance properties. However, if the Cu content is too high, copper is prone to becoming brittle. P can improve the corrosion resistance of rebar, and when it acts in combination with Cu, it achieves the optimal effect. If the P content is too high, the cold brittleness of steel will be improved. S and Cu can form dense CuS, which can prevent the penetration of erosive media, which is favorable for improving corrosion resistance properties. S and Mn are easy to generate inclusions, but CuS is easier to form than MnS. Therefore, an appropriate amount of S element is a beneficial element for the present invention, and when combined with Cu, it can improve corrosion resistance.
[0021] Ti is both a corrosion-resistant element and a strengthening element, which can improve the corrosion potential and corrosion resistance of steel, and can improve the mechanical properties of steel through fine grain strengthening. If the Ti content is too high, oxides will be easily generated, which will cause nozzle clogging during continuous casting. Al is deoxidized during the smelting process, which reduces the oxygen content in the molten steel, and Al can form oxides in the steel, which can be concentrated in the rust layer to improve the corrosion resistance properties, but if its content is too high, it will cause nozzle clogging during continuous casting. V and Nb are both strengthening elements, which can form carbonitrides in the steel, which can improve the mechanical properties of steel through fine grain strengthening and precipitation strengthening, and this strengthening effect is related to the content of C and N.
[0022] In the present invention, the composition of low carbon alloy steel is used, and each element is comprehensively designed and the content of each element is adjusted to fully exert the corrosion resistance and strengthening effect of each element, and the alloy ratio and multi-phase structure are precisely controlled to solve the problem of the prior art that the corrosion resistance, mechanical properties and low cost cannot be achieved at the same time.
[0023] 2. In the production process of the corrosion-resistant rebar according to the present invention, the corrosion-resistant rebar produced by this production process has good chlorine salt corrosion resistance without adding Cr, Ni, and Mo, so the cost is low and the difficulty of the production process is low. The structure of the rebar obtained by this process is pearlite and ferrite, with the proportion of ferrite being 50-75%, the yield strength being 400MPa or more, the elongation after fracture being 30% or more, the maximum strength total elongation being 20% or more, the tensile strength to yield strength ratio being 1.30 or more, and the relative corrosion rate is 35% or less compared to normal rebar HRB400 in a chlorine salt corrosion environment (5% NaCl, 35°C, humidity 70%).
[0024] 3. In the production process of corrosion-resistant rebar according to this application, by controlling the type and method of alloy addition during the rebar production process, fine control of multi-element alloy content and low-cost production are achieved, and by using the controlled rolling and controlled cooling process (heating temperature of the slab, temperature of the rebar transferred to the cooling bed, etc.), the ferrite / pearlite multi-phase structure is controlled, ensuring the strengthening effect of alloy elements, and optimizing the corrosion resistance and strength-plasticity compatibility of the rebar, thereby developing low-cost, highly corrosion-resistant alloy rebar.
[0025] The tapping temperature in the smelting process of the present invention is set to (1) ensure that the scrap steel is completely melted during smelting, and (2) ensure that the molten steel has the same temperature as when it starts to be refined, because adding alloys during the smelting and tapping process reduces the temperature of the molten steel, which affects the refining temperature. In the present invention, the smelting process is controlled to achieve efficient smelting and fine composition control.
[0026] Ferrophosphorus is an element that is easily oxidized, so it is added during the refining process, and if it is added at other stages, the element yield will be low. The refining steel discharge temperature is 1580-1600℃, and this temperature is related to the continuous casting temperature, because the refining temperature determines the continuous casting temperature, and the continuous casting temperature is calculated based on the alloy composition and is directly related to the content of each element in the rebar.
[0027] Low carbon steel mold powder is used in continuous casting, and the thickness of the mold powder layer is 8-10mm. It has the following advantages: (1) It reduces the influence of carbon in the mold powder on the carbon content in the molten steel, ensures fine control of the carbon content of the final product, meets the requirements for low carbon, and prevents carbides from affecting the corrosion resistance properties; (2) The mold powder layer can reduce the contact and convection between the molten steel and the air, and maintain the stability of the molten steel temperature. The electromagnetic stirring parameters are closely related to the uniformity of the molten steel composition. The product of this application is a corrosion-resistant steel, and the higher the purity of the molten steel, the better the corrosion resistance. The water flow rate of the crystallizer mainly functions to cool. Because the cross-sectional size of the blank is large, there is a temperature difference between the surface and the core, and if the water flow rate ratio is not appropriate, the surface quality will be poor and defects such as cracks will occur. The drawing speed is affected by the temperature of the molten steel, the cooling capacity, etc. An appropriate drawing speed can ensure a highly uniform cast piece, while also avoiding steel breakouts.
[0028] The heating temperature of the slab affects the dissolution of alloy elements and the size of crystal grains, which has a significant effect on the structure and mechanical properties of the product. This parameter is determined based on the alloy composition (melting temperature of elements) and the size of the crystal grains. The temperature of the rebar transferred to the cooling bed is related to the cooling method and is mainly designed based on the continuous cooling curve of the rebar supercooled austenite. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The following examples are provided for a better understanding of the present application, but are not limited to the best embodiment, and are not intended to limit the content and scope of protection of the present application. Any products that are the same or similar to those of the present application obtained by the suggestions of the present application or by combining the features of the present application with other prior art will fall within the scope of protection of the present application.
[0030] Unless specific experimental procedures or conditions are specified in the examples, they may be carried out according to the operations or conditions of the general experimental procedures described in the literature in this field. If the manufacturers of the reagents or instruments used are not specified, they are all general reagent products available commercially.
[0031] The following specific examples contain, by weight percent, C: 0.03-0.15%, Si: 0.8-2.0%, Mn: 0.8-2.0%, Cu: 0.10-0.50%, P: 0.08-0.2%, S: 0.005-0.01%, Nb≦0.1%, V≦0.2%, Ti≦0.1%, Al≦0.1%, and the remainder being Fe and unavoidable impurities. To provide a corrosion-resistant reinforcing bar having 0.6≦Si / Mn≦2.0 and 0.25%≦Cu+P+S≦0.62%.
[0032] Optionally, C is 0.05-0.12%, and further optionally 0.06-0.09%; Si is 0.9-1.7%, and optionally 1.0-1.3%; Mn is 0.9-1.8%, and optionally 1.0-1.5%; Cu is 0.2-0.3%. P is 0.11-0.18%, and optionally 0.13-0.17%.
[0033] The production process of the above corrosion-resistant rebar includes the following steps: Smelting: The molten steel is smelted in a converter and the tapping temperature is set to 1600 The temperature was set to 1640°C, and for deoxidation alloying at tapping, alloy and flux were added in the order of silico-manganese-ferrosilicon-lime, with the amount of silico-manganese added being 10-30kg / t and the amount of ferrosilicon added being 15-30kg / t based on 1 ton of molten steel. Before tapping, the argon gas bottom injection control valve of the tundish was opened, and argon gas was injected throughout the tapping process, with the bottom injection pressure being 0.4-0.5MPa in the early stage and 0.3-0.4MPa in the later stage. Refining: When refining, ferrophosphorus and copper plate are added, the refining soft stirring time is 10 minutes or more, and the steel tapping temperature is 1580-1600°C. Based on 1 ton of molten steel, the amount of ferrophosphorus added is 3-6 kg / t, the phosphorus content in the ferrophosphorus is 20-25 wt%, and the amount of copper plate added is 1.5-3.5 kg / t. Continuous casting: low carbon steel mold powder is used, mold powder layer thickness 8~10mm, drawing speed 2.5~3.5m / min, crystallizer water flow rate 1950~2050L / min, at the crystallizer electromagnetic stirring current 330A~370A, frequency 3~5Hz, at the end electromagnetic stirring current 380A~420A, frequency 10~12Hz. Slab heating: The heating temperature is 1200 to 1250°C. Continuous hot rolling: The temperature of the reinforcing bar transferred to the cooling bed is set to 850-900°C, and the reinforcing bar is naturally cooled to room temperature after rolling. Controlling the cooling rate after rolling and the temperature of the reinforcing bar transferred to the cooling bed is advantageous for obtaining a suitable structure.
[0034] Example 1 This embodiment contains, by weight, C: 0.06%, Si: 1.0%, Mn: 1.0%, Cu: 0.2%, P: 0.13%, S: 0.005%, Nb: 0.075%, and the remainder is Fe and unavoidable impurities. The present invention provides a corrosion-resistant rebar having a Si / Mn ratio of 1.0 and a Cu+P+S ratio of 0.34%. The method for producing the corrosion-resistant rebar includes the following steps: Smelting process: Molten steel is smelted in a converter, the tapping temperature is set to 1630℃, and silico-manganese (FeMn 65 S 17 ) 20kg / t, and ferrosilicon (FeSi 72 Argon gas was blown throughout the tapping process, and the bottom blowing pressure was controlled at 0.4 MPa in the early stage and 0.3 MPa in the later stage. Refining process: ferrophosphorus (P content 23%, added amount 4kg / t), copper plate (Cu content 99%, added amount 1.5kg / t), ferroniobium (Nb content 65%, added amount 1.2kg / t), refining soft stirring time 12min, continuous pouring steel temperature 1600℃. Continuous casting process: mold powder layer thickness 8mm, drawing speed 2.8m / min, water flow rate of crystallizer 2000±50L / min, electromagnetic stirring current 350A, frequency 3Hz in crystallizer, electromagnetic stirring current 400A, frequency 10Hz at the end, cast piece cross-sectional size 140mm×140mm (width×height). Slab heating and hot continuous rolling process: The heating temperature was 1220°C, the temperature of the rebar transferred to the cooling bed was 880°C, and after rolling, it was naturally cooled to room temperature, and the rebar diameter was 20 mm.
[0035] Example 2 This embodiment contains, by weight, C: 0.08%, Si: 1.28%, Mn: 1.0%, Cu: 0.25%, P: 0.15%, S: 0.005%, V: 0.15%, and the remainder is Fe and unavoidable impurities. A corrosion-resistant rebar having Si / Mn=1.28 and Cu+P+S=0.41% is provided. The method for producing the above corrosion-resistant rebar includes the following steps. Smelting process: The molten steel is smelted in a converter, the tapping temperature is set to 1630℃, and silico-manganese (FeMn 65 S 17 ) 20kg / t, and ferrosilicon (FeSi 72 Argon gas was blown throughout the tapping process, and the bottom blowing pressure was controlled at 0.42 MPa in the early stage and 0.32 MPa in the later stage. Refining process: Ferrophosphorus (P content 23%, added amount 4.5kg / t), copper plate (Cu content 99%, added amount 1.8kg / t), ferrovanadium (V content 48%, added amount 3.3kg / t) are added, refining soft stirring time is 13min, continuous pouring steel temperature is 1595℃. Continuous casting process: mold powder layer thickness 10mm, drawing speed 3.0m / min, water flow rate of crystallizer 2000±50L / min, electromagnetic stirring current 330A, frequency 5Hz in crystallizer, electromagnetic stirring current 390A, frequency 10Hz at the end, cast piece cross-sectional size 140mm×140mm (width×height). Slab heating and hot continuous rolling process: The heating temperature was 1250°C, the temperature of the rebar transferred to the cooling bed was 890°C, and after rolling, it was naturally cooled to room temperature, and the rebar diameter was 28 mm.
[0036] Example 3 This embodiment contains, by weight, C: 0.09%, Si: 1.3%, Mn: 1.5%, Cu: 0.3%, P: 0.17%, S: 0.01%, Nb: 0.10%, Ti: 0.01%, Al: 0.01%, and the remainder is Fe and unavoidable impurities. A corrosion-resistant rebar having Si / Mn=0.87 and Cu+P+S=0.48 is provided. The method for producing the above corrosion-resistant rebar includes the following steps. Smelting process: The molten steel is smelted in a converter, the tapping temperature is set to 1630℃, and silico-manganese (FeMn 65 S 17 ) 25kg / t, and ferrosilicon (FeSi 72 Argon gas was blown throughout the tapping process, and the bottom blowing pressure was controlled at 0.45 MPa in the early stage and 0.35 MPa in the later stage. Refining process: ferrophosphorus (P content 23%, added amount 5kg / t), copper plate (Cu content 99%, added amount 2.0kg / t), ferroniobium (Nb content 65%, added amount 1.6kg / t), ferrotitanium (Ti content 30%, added amount 0.5kg / t), aluminum particles (Al content 99%, added amount 0.15kg / t), refining soft stirring time 15min, continuous pouring and tapping steel temperature 1595℃. Continuous casting process: mold powder layer thickness 9mm, drawing speed 2.6m / min, water flow rate of crystallizer 2000±50L / min, electromagnetic stirring current 370A, frequency 3.5Hz in crystallizer, electromagnetic stirring current 420A, frequency 11Hz at the end, cast piece cross-sectional size 140mm×140mm (width×height). Slab heating and hot continuous rolling process: The heating temperature was 1200°C, and the temperature of the rebar transferred to the cooling bed was 900°C. After rolling, the rebar was naturally cooled to room temperature, and the diameter of the rebar was 32 mm.
[0037] Example 4 This embodiment contains, by weight, C: 0.05%, Si: 0.9%, Mn: 1.49%, Cu: 0.5%, P: 0.11%, S: 0.01%, Nb: 0.03%, V: 0.15%, and the remainder is Fe and unavoidable impurities. A corrosion-resistant rebar having Si / Mn=0.60 and Cu+P+S=0.62 is provided. The method for producing the above corrosion-resistant rebar includes the following steps. Smelting process: The molten steel is smelted in a converter, the tapping temperature is set to 1630℃, and silico-manganese (FeMn 65 S 17 ) 25kg / t, and ferrosilicon (FeSi 72 Argon gas was blown throughout the tapping process, and the bottom blowing pressure was controlled at 0.4 MPa in the early stage and 0.3 MPa in the later stage. Refining process: ferrophosphorus (P content 23%, added amount 3.5kg / t), copper plate (Cu content 99%, added amount 3.5kg / t), ferroniobium (V content 65%, added amount 0.5kg / t), ferrovanadium (V content 48%, added amount 3.3kg / t), refining soft stirring time 11min, continuous pouring steel temperature 1600℃. Continuous casting process: mold powder layer thickness 8mm, drawing speed 3.5m / min, water flow rate of crystallizer 2000±50L / min, electromagnetic stirring current 350A, frequency 5Hz in crystallizer, electromagnetic stirring current 380A, frequency 12Hz at the end, cast piece cross-sectional size 140mm×140mm (width×height). Slab heating and hot continuous rolling process: The heating temperature was 1250°C, the temperature of the rebar transferred to the cooling bed was 850°C, and after rolling, it was naturally cooled to room temperature, and the rebar diameter was 16 mm.
[0038] Example 5 This embodiment contains, by weight, C: 0.12%, Si: 1.7%, Mn: 0.9%, Cu: 0.1%, P: 0.18%, S: 0.01%, Ti: 0.1%, and the remainder is Fe and unavoidable impurities. A corrosion-resistant rebar having Si / Mn=1.89 and Cu+P+S=0.29 is provided. The method for producing the above corrosion-resistant rebar includes the following steps. Smelting process: The molten steel is smelted in a converter, the tapping temperature is set to 1630℃, and silico-manganese (FeMn 65 S 17 ) 11kg / t, and ferrosilicon (FeSi 72 Argon gas was blown throughout the tapping process, and the bottom blowing pressure was controlled at 0.5 MPa in the early stage and 0.4 MPa in the later stage. Refining process: ferrophosphorus (P content 23%, added amount 5.5kg / t), copper plate (Cu content 99%, added amount 1.5kg / t), ferrotitanium (Ti content 30%, added amount 5kg / t), refining soft stirring time 15min, continuous pouring steel temperature 1590℃. Continuous casting process: mold powder layer thickness 10mm, drawing speed 2.5m / min, water flow rate of crystallizer 2000±50L / min, electromagnetic stirring current 350A, frequency 5Hz in crystallizer, electromagnetic stirring current 400A, frequency 12Hz at the end, cast piece cross-sectional size 140mm×140mm (width×height). Slab heating and hot continuous rolling process: The heating temperature was 1250°C, the temperature of the rebar transferred to the cooling bed was 880°C, and after rolling, it was naturally cooled to room temperature, and the rebar diameter was 10 mm.
[0039] Example 6 This embodiment contains, by weight, C: 0.03%, Si: 0.8%, Mn: 0.8%, Cu: 0.3%, P: 0.08%, S: 0.005%, V: 0.2%, Ti: 0.01%, Al: 0.01%, and the remainder is Fe and unavoidable impurities. A corrosion-resistant rebar having Si / Mn=1 and Cu+P+S=0.39% is provided. The method for producing the above corrosion-resistant rebar includes the following steps. Smelting process: The molten steel is smelted in a converter, the tapping temperature is set to 1610℃, and silico-manganese (FeMn 65 S 17 ) 10kg / t, and ferrosilicon (FeSi 72 Argon gas was blown throughout the tapping process, and the bottom blowing pressure was controlled at 0.4 MPa in the early stage and 0.3 MPa in the later stage. Refining process: ferrophosphorus (P content 23%, added amount 3kg / t), copper plate (Cu content 99%, added amount 2kg / t), ferrovanadium (V content 48%, added amount 4kg / t), ferrotitanium (Ti content 30%, added amount 0.5kg / t), aluminum particles (Al content 99%, added amount 0.15kg / t), refining soft stirring time 10min, continuous pouring steel temperature 1595℃. Continuous casting process: mold powder layer thickness 9.5mm, drawing speed 2.6m / min, water flow rate of crystallizer 2000±50L / min, electromagnetic stirring current 345A, frequency 3.5Hz in crystallizer, electromagnetic stirring current 405A, frequency 11Hz at the end, cast piece cross-sectional size 140mm×140mm (width×height). Slab heating and hot continuous rolling process: The heating temperature was 1200°C, and the temperature of the rebar transferred to the cooling bed was 900°C. After rolling, the rebar was naturally cooled to room temperature, and the rebar diameter was 18 mm.
[0040] Example 7 This embodiment contains, by weight, C: 0.15%, Si: 2%, Mn: 2%, Cu: 0.25%, P: 0.2%, S: 0.01%, Al: 0.1%, and the remainder is Fe and unavoidable impurities. A corrosion-resistant rebar having Si / Mn=1 and Cu+P+S=0.46 is provided. The method for producing the above corrosion-resistant rebar includes the following steps. Smelting process: The molten steel is smelted in a converter, the tapping temperature is set to 1640°C, and silico-manganese (FeMn 65 S 17 ) 30kg / t, and ferrosilicon (FeSi 72 Argon gas was blown throughout the tapping process, and the bottom blowing pressure was controlled at 0.5 MPa in the early stage and 0.4 MPa in the later stage. Refining process: ferrophosphorus (P content 23%, added amount 6kg / t), copper plate (Cu content 99%, added amount 1.8kg / t), aluminum particles (Al content 99%, added amount 1.5kg / t), refining soft stirring time 15min, continuous pouring steel temperature 1600℃. Continuous casting process: mold powder layer thickness 8.5mm, drawing speed 2.6m / min, water flow rate of crystallizer 2000±50L / min, electromagnetic stirring current 350A, frequency 5Hz in crystallizer, electromagnetic stirring current 410A, frequency 12Hz at the end, cast piece cross-sectional size 140mm×140mm (width×height). Slab heating and hot continuous rolling process: The heating temperature was 1250°C, the temperature of the rebar transferred to the cooling bed was 900°C, and after rolling, it was naturally cooled to room temperature, and the rebar diameter was 25 mm.
[0041] Example 8 This embodiment contains, by weight, C: 0.08%, Si: 2%, Mn: 1%, Cu: 0.145%, P: 0.1%, S: 0.005%, Nb: 0.05%, V: 0.05%, Ti: 0.1%, Al: 0.1%, and the remainder is Fe and unavoidable impurities. Provide a corrosion-resistant rebar with Si / Mn=2 and Cu+P+S=0.25. The method for producing the above corrosion-resistant rebar includes the following steps. Smelting process: The molten steel is smelted in a converter, the tapping temperature is set to 1630℃, and silico-manganese (FeMn 65 S 17 ) 20kg / t, and ferrosilicon (FeSi 72 Argon gas was blown throughout the tapping process, and the bottom blowing pressure was controlled at 0.4 MPa in the early stage and 0.3 MPa in the later stage. Refining process: ferrophosphorus (P content 23%, added amount 3.5kg / t), copper plate (Cu content 99%, added amount 1.9kg / t), ferroniobium (Nb content 65%, added amount 0.8kg / t), ferrovanadium (V content 48%, added amount 1kg / t), ferrotitanium (Ti content 30%, added amount 5kg / t), aluminum particles (Al content 99%, added amount 1.5kg / t), refining soft stirring time 15min, continuous pouring steel temperature 1600℃. Continuous casting process: mold powder layer thickness 10mm, drawing speed 2.6m / min, water flow rate of crystallizer 2000±50L / min, electromagnetic stirring current 350A, frequency 5Hz in crystallizer, electromagnetic stirring current 395A, frequency 12Hz at the end, cast piece cross-sectional size 140mm×140mm (width×height). Slab heating and hot continuous rolling process: The heating temperature was 1250°C, the temperature of the rebar transferred to the cooling bed was 900°C, and after rolling, it was naturally cooled to room temperature, and the rebar diameter was 28 mm.
[0042] Comparative Example 1 This comparative example contains, by weight, C: 0.25%, Si: 0.5%, Mn: 1.5%, Cu: 0.3%, P: 0.035%, S: 0.0035%, Nb: 0.05%, Ti: 0.1%, and the remainder is Fe and unavoidable impurities. A corrosion-resistant rebar having Si / Mn=0.33 and Cu+P+S=0.34% is provided. The method for producing the above corrosion-resistant rebar includes the following steps. Smelting process: The molten steel is smelted in a converter, the tapping temperature is set to 1600°C, and silico-manganese (FeMn 65 S 17 ) 20kg / t, and ferrosilicon (FeSi 72 Argon gas was blown throughout the tapping process, and the bottom blowing pressure was controlled at 0.4 MPa in the early stage and 0.3 MPa in the later stage. Refining process: no ferrophosphorus added, copper plate (Cu content 99%, added amount 2kg / t), ferroniobium (Nb content 65%, added amount 0.8kg / t), ferrotitanium (Ti content 30%, added amount 5kg / t), refining soft stirring time 15min, continuous pouring steel temperature 1600℃. Continuous casting process: mold powder layer thickness 8mm, drawing speed 2.6m / min, water flow rate of crystallizer 2000±50L / min, electromagnetic stirring current 350A, frequency 4Hz in crystallizer, electromagnetic stirring current 400A, frequency 11Hz at the end, cast piece cross-sectional size 140mm×140mm (width×height). Slab heating and hot continuous rolling process: The heating temperature was 1250°C, the temperature of the rebar transferred to the cooling bed was 900°C, and after rolling, it was naturally cooled to room temperature, and the rebar diameter was 25 mm.
[0043] Comparative Example 2 This comparative example contains, by weight, C: 0.08%, Si: 2.5%, Mn: 0.5%, P: 0.035%, S: 0.0035%, V: 0.15%, Ti: 0.1%, Al: 0.1%, and the remainder is Fe and unavoidable impurities. A corrosion-resistant rebar having Si / Mn=5 and Cu+P+S=0.04% is provided. The method for producing the above corrosion-resistant rebar includes the following steps. Smelting process: The molten steel is smelted in a converter, the tapping temperature is set to 1600°C, and silico-manganese (FeMn 65 S 17 ) 8kg / t, and ferrosilicon (FeSi 72 Argon gas was blown throughout the tapping process, and the bottom blowing pressure was controlled at 0.5 MPa in the early stage and 0.4 MPa in the later stage. Refining process: no ferrophosphorus or copper plate added, ferrovanadium (V content 48%, added amount 3kg / t), ferrotitanium (Ti content 30%, added amount 5kg / t), aluminum particles (Al content 99%, added amount 1.5kg / t), refining soft stirring time 15min, continuous pouring steel temperature 1590℃. Continuous casting process: mold powder layer thickness 10mm, drawing speed 2.5m / min, water flow rate of crystallizer 2000±50L / min, electromagnetic stirring current 350A, frequency 4Hz in crystallizer, electromagnetic stirring current 400A, frequency 11Hz at the end, cast piece cross-sectional size 140mm×140mm (width×height). Slab heating and hot continuous rolling process: The heating temperature was 1200°C, the temperature of the rebar transferred to the cooling bed was 850°C, and after rolling, it was naturally cooled to room temperature, and the rebar diameter was 20 mm.
[0044] Comparative Example 3 This comparative example contains, by weight, C: 0.25%, Si: 0.6%, Mn: 2.5%, Cu: 0.5%, P: 0.2%, S: 0.01%, V: 0.15%, Ti: 0.1%, and the remainder is Fe and unavoidable impurities. A corrosion-resistant rebar having Si / Mn=0.24 and Cu+P+S=0.71 is provided. The method for producing the above corrosion-resistant rebar includes the following steps. Smelting process: The molten steel is smelted in a converter, the tapping temperature is set to 1600°C, and silico-manganese (FeMn 65 S 17 ) 35kg / t, and ferrosilicon (FeSi 72 Argon gas was blown throughout the tapping process, and the bottom blowing pressure was controlled at 0.5 MPa in the early stage and 0.4 MPa in the later stage. Refining process: ferrophosphorus (P content 23%, added amount 6kg / t), copper plate (Cu content 99%, added amount 3.5kg / t), ferrovanadium (V content 48%, added amount 3kg / t), ferrotitanium (Ti content 30%, added amount 5kg / t), refining soft stirring time 15min, continuous pouring steel temperature 1610℃. Continuous casting process: mold powder layer thickness 5mm, drawing speed 2.5m / min, water flow rate of crystallizer 2000±50L / min, electromagnetic stirring current 350A, frequency 4Hz in crystallizer, electromagnetic stirring current 400A, frequency 11Hz at the end, cast piece cross-sectional size 140mm×140mm (width×height). Slab heating and hot continuous rolling process: The heating temperature was 1250°C, the temperature of the rebar transferred to the cooling bed was 880°C, and after rolling, it was naturally cooled to room temperature, and the rebar diameter was 16 mm.
[0045] Comparative Example 4 This comparative example contains, by weight, C: 0.25%, Si: 2.5%, Mn: 2.5%, Cu: 1%, P: 0.2%, S: 0.01%, Nb: 0.05%, Ti: 0.1%, Al: 0.1%, and the remainder is Fe and unavoidable impurities. Provide a corrosion-resistant rebar with Si / Mn=1 and Cu+P+S=1.21. The method for producing the above corrosion-resistant rebar includes the following steps. Smelting process: The molten steel is smelted in a converter, the tapping temperature is set to 1640°C, and silico-manganese (FeMn 65 S 17 ) 35kg / t, and ferrosilicon (FeSi 72 Argon gas was blown throughout the tapping process, and the bottom blowing pressure was controlled at 0.5 MPa in the early stage and 0.4 MPa in the later stage. Refining process: ferrophosphorus (P content 23%, added amount 6kg / t), copper plate (Cu content 99%, added amount 4kg / t), ferroniobium (Nb content 65%, added amount 0.8kg / t), ferrotitanium (Ti content 30%, added amount 5kg / t), aluminum particles (Al content 99%, added amount 1.5kg / t), refining soft stirring time 15min, continuous pouring and tapping steel temperature 1610℃. Continuous casting process: mold powder layer thickness 11mm, drawing speed 2.5m / min, water flow rate of crystallizer 2000±50L / min, electromagnetic stirring current 350A, frequency 5Hz in crystallizer, electromagnetic stirring current 400A, frequency 12Hz at the end, cast piece cross-sectional size 140mm×140mm (width×height). Slab heating and hot continuous rolling process: The heating temperature was 1250°C, the temperature of the rebar transferred to the cooling bed was 900°C, and after rolling, it was naturally cooled to room temperature, and the rebar diameter was 32 mm.
[0046] Comparative Example 5 This comparative example contains, by weight, C: 0.15%, Si: 0.7%, Mn: 1.35%, Cu: 0.3%, P: 0.015%, S: 0.005%, Nb: 0.015%, Cr: 1.35%, Ni: 0.3%, Mo: 0.1%, and the remainder is Fe and unavoidable impurities. A corrosion-resistant rebar having Si / Mn=0.52 and Cu+P+S=0.32 is provided. The method for producing the above corrosion-resistant rebar includes the following steps. Smelting process: The molten steel is smelted in a converter, the tapping temperature is set to 1630℃, and silico-manganese (FeMn 65 S 17 ) 27kg / t, Ferro-silicon (FeSi 72) 14kg / t, ferrochromium (Cr content 65%) 30kg / t, and ferromolybdenum (Mo content 55%) 3kg / t were added. Argon gas was blown throughout the tapping process, and the bottom blowing pressure was controlled at 0.4MPa in the early stage and 0.3MPa in the later stage. Refining process: Ferrophosphor (P content 23%, addition amount 1kg / t), copper plate (Cu content 99%, addition amount 2kg / t), ferroniobium (Nb content 65%, addition amount 0.3kg / t), nickel plate (nickel content 99%, 2kg / t), refining soft stirring time 12min, continuous pouring steel temperature 1600℃. Continuous casting process: mold powder layer thickness 8mm, drawing speed 2.8m / min, water flow rate of crystallizer 2000±50L / min, electromagnetic stirring current 350A, frequency 3Hz in crystallizer, electromagnetic stirring current 400A, frequency 10Hz at the end, cast piece cross-sectional size 140mm×140mm (width×height). Slab heating and hot continuous rolling process: The heating temperature was 1220°C, the temperature of the rebar transferred to the cooling bed was 880°C, and after rolling, it was naturally cooled to room temperature, and the rebar diameter was 20 mm.
[0047] Test Example This test example provides the properties of the reinforcing bars obtained in each of the Examples and Comparative Examples, and the details are as follows. The test method of yield strength was based on the national standard GB / T228.1-2010 Metallic Material Tensile Test Part 1: Room Temperature Test Method, and the tensile strength-yield strength ratio was calculated. Tensile strength-yield strength ratio = tensile strength / yield strength. The test results are shown in Table 1. Test method for tensile strength: refer to national standard GB / T228.1-2010 Metallic material tensile test Part 1. Test method for elongation after break: refer to national standard GB / T228.1-2010 Metallic material tensile test Part 1. Maximum force total elongation: Refer to national standard GB / T228.1-2010 Metallic material tensile test Part 1. Corrosion rate relative value: The corrosion resistance of the corrosion-resistant rebars manufactured in the examples and comparative examples was tested for chlorine salt corrosion resistance, and the improvement factor of the corrosion resistance of the corrosion-resistant rebars was calculated in comparison with the model HRB400 rebar. The specific test method is as follows. A corrosion-resistant rebar with a length of 100 mm was cut out and turned using a lathe to obtain a test sample with a diameter of 10 mm. The test sample was placed in a corrosive solution under conditions of a temperature of 35°C and a humidity of 70%, and a salt spray corrosion test was performed. The test corrosive solution was a 5 wt% sodium chloride solution with a pH of 7.0, and the test time was 14 days. The weight of the test sample before and after corrosion was measured using an electronic microbalance. The calculation formula is: Corrosion rate relative value = (weight change before and after corrosion of corrosion-resistant rebar / weight change before and after corrosion of HRB400) x 100%. Ferrite and pearlite test method: Using a Zeiss optical microscope, the types of structures of the corrosion-resistant rebars manufactured in the examples and comparative examples were observed at a magnification of 200 times, and the volumetric proportion of ferrite was calculated. Under the optical microscope, ferrite appears white and pearlite appears black. The volumetric proportion of each structure per unit area was calculated from this difference in color. The results are shown in Tables 1 and 2.
[0048] [Table 1]
[0049] [Table 2]
[0050] As can be seen from the above results, the present invention can have good corrosion resistance without adding Cr, Ni, or Mo, and the corrosion-resistant rebar of the present invention can combine corrosion resistance, mechanical properties, and low cost. Furthermore, the relative corrosion rate of the corrosion-resistant rebar of the present invention is 35% or less.
[0051] From Comparative Examples 1 to 4, it was found that in the present application, by controlling Si / Mn and Cu+P+S, the rebar can have good corrosion resistance, mechanical properties, and strength-plasticity compatibility. In comparison with Comparative Example 5, it was found that the rebar according to the present application has better mechanical properties such as elongation after fracture and maximum strength total elongation compared to the rebar containing Cr. This shows that in the present application, it is possible to obtain a rebar with excellent strength and mechanical properties at a lower cost without adding Cr, Ni, and Mo.
[0052] Obviously, the above examples are merely examples given for clarity and are not intended to limit the embodiments. Those skilled in the art may make other different changes or modifications based on the above description. It is not necessary to cover all the embodiments here, and it is impossible to cover them all. Moreover, obvious changes or variations derived therefrom are still within the scope of protection of the present application.
Claims
1. The composition contains, by weight, C: 0.03-0.15%, Si: 0.8-2.0%, Mn: 0.8-2.0%, Cu: 0.10-0.50%, P: 0.08-0.2%, S: 0.005-0.01%, Nb≦0.1%, V≦0.2%, Ti≦0.1%, Al≦0.1%, and the balance being Fe and unavoidable impurities. A corrosion-resistant reinforcing bar characterized in that 0.6≦Si / Mn≦2.0 and 0.25%≦Cu+P+S≦0.62%.
2. (1) The C content is 0.05 to 0.12%; (2) The Si content is 0.9 to 1.7%; (3) The Mn content is 0.9 to 1.8%; (4) The Cu content is 0.2 to 0.3%; (5) The P content is 0.11 to 0.18%; The corrosion-resistant reinforcing bar according to claim 1, characterized in that it satisfies at least one of the following requirements.
3. (1) The C content is 0.06 to 0.09%; (2) The Si content is 1.0 to 1.3%; (3) The Mn content is 1.0 to 1.5%; (4) The P content is 0.13 to 0.17%; The corrosion-resistant reinforcing bar according to claim 1 or 2, characterized in that it satisfies at least one of the above requirements.
4. 4. The method for producing a corrosion-resistant reinforcing bar according to claim 1, further comprising the steps of smelting, refining, continuous casting, slab heating, and continuous hot rolling.
5. The continuous casting process includes: (1) A low-carbon steel mold powder is used, the thickness of the mold powder layer is 8-10 mm, and the carbon content of the low-carbon steel is not more than 0.15%; (2) The water flow rate of the crystallizer is 1950 to 2050 L / min; (3) The crystallizer has an electromagnetic stirring current of 330A-370A and a frequency of 3-5Hz, and the terminal has an electromagnetic stirring current of 380A-420A and a frequency of 10-12Hz; (4) The drawing speed is 2.5 to 3.5 m / min.
5. The method according to claim 4, wherein at least one of the following is satisfied:
6. The smelting process includes: (1) The tapping temperature is 1600 to 1640°C. (2) For the deoxidation of steel at tapping, silico-manganese, ferrosilicon and lime are added in this order; The amount of the silicomanganese added is 10 to 30 kg / t, and the amount of the ferrosilicon added is 15 to 30 kg / t; (3) The bottom blowing pressure is 0.4-0.5 MPa in the early stage and 0.3-0.4 MPa in the later stage.
6. The method according to claim 4, wherein at least one of the following conditions is satisfied:
7. The production method according to claim 4 or 5, characterized in that in the slab heating step, the heating temperature is 1200 to 1250°C.
8. The method according to claim 4 or 5, characterized in that in the hot continuous rolling process, the temperature of the reinforcing bar transferred to the cooling bed is 850 to 900°C.
9. The refining step includes: (1) the smelting process includes the step of adding ferrophosphorus and copper; (2) The stirring time of the refining is 10 minutes or more; (3) The tapping temperature is 1580 to 1600°C.
6. The method according to claim 4, wherein at least one of the following conditions is satisfied:
10. The phosphorus content in the ferrophosphorus is 20 to 25% by mass, The amount of ferrophosphorus added is 3 to 6 kg / t, 10. The method according to claim 9, wherein the amount of copper added is 1.5 to 3.5 kg / t.
Citation Information
Patent Citations
Short flow 500 MPa level weather-resistant anti-seismic reinforcing steel bar and preparation method thereof
CN112458381A
Preparation method of 400MPa-grade industrial atmosphere corrosion-resistant reinforcing steel bar
CN113293334A
400MPa-grade microalloyed corrosion-resistant steel bar and production method thereof
CN114196884A
Enameled product and glaze
JP2007217789A
Steel bar or steel product, and manufacturing method therefor
JP2020002455A